Pengambilan Keputusan dalam Mengatasi Kekurangan Sumber Daya Manusia di UMKM Konveksi Indra Jaya - Yulianto, Didik; Sopian, Pandi; Aziz, Diaz Fathul; Afriansyah, Reza; Suherman, Ujang (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This article discusses the decision-making process in overcoming the shortage of human resources in the Indra Jaya convection as MSMEs. This study was conducted to explore the challenges MSMEs faced in recruiting and managing the workforce and to identify the strategies implemented by managers in dealing with these problems. The research method used was qualitative, with data collection through interviews, observations, and literature studies. The study results indicate that MSMEs face difficulties finding new employees who meet the required criteria, thus requiring stricter recruitment procedures and clear standards. In addition, this article also describes the various decision-making styles used, such as autocratic, participatory, and delegative, as well as systematic steps in the decision-making process. The data collected will be analyzed using thematic analysis techniques to understand how managers carry out decision-making to overcome human resource shortages. These findings are expected to provide insight for MSME owners in improving the effectiveness of HR management to support business sustainability.